PROGRAM GERAKAN 1 HARI 2 TELUR DALAM MENINGKATKAN PENGETAHUAN PENCEGAHAN STUNTING PADA KADER POSYANDU - Pratidina, Ginung; Rahman, Febrian Batara Aditya; Rahmadhina, Jestiana Al Kayrani; Lestari, Anggie Septia; Tirta, Maura Najwa Noor Raina; Salim, Diaz Sya’bania; Ilmi, Lu’lu’; Nurhazizah, Refina; Febriansyah, Febriansyah; Arifin, Abin Riyan; Rahmadina, Rahmadina; Ikraami , Reksa Dzul (Universitas Islam 45 Bekasi, 2025)
Stunting remains a major public health challenge in Indonesia. One of the main contributing factors is the low intake of animal protein among children, thereby requiring simple yet effective community-based nutritional interventions. This community service activity aimed to improve the knowledge of posyandu (integrated health post) cadres regarding stunting prevention through the implementation of the One Day Two Eggs Movement. The program was carried out by providing nutrition education on the importance of animal protein consumption, particularly eggs, using interactive lectures, group discussions, and simple demonstrations. A total of 50 posyandu cadres participated in the activity and were assessed using pre-test and post-test instruments to measure knowledge levels before and after the intervention. The results showed an increase in the average knowledge scores of participants following the program, indicating the effectiveness of the One Day Two Eggs Movement in enhancing understanding of the role of animal protein in stunting prevention. Furthermore, participants demonstrated strong enthusiasm to apply and disseminate the acquired information within their respective communities. Based on these findings, the One Day Two Eggs Movement can be recommended as a practical community-based educational strategy that is easy to implement, provides direct impact, and holds potential to be integrated with posyandu activities as well as maternal and child health programs in a sustainable manner.